(Pendidikan Kesehatan yang Menginspirasi: Peran Audio Visual dalam Meningkatkan Pengetahuan tentang Risiko Pernikahan Dini) - Azza, Aya Aslama; Suhariyati, Suhariyati; Aris, Arifal; Sholikhah, Siti (Jurnal Surya, 2025)
Introduction: Early marriage is a problem that has a significant impact on the physical, mental, and social health of adolescents. One of the main factors influencing early marriage is the low knowledge of adolescents about the risks and impacts. This study aims to determine the effect of health education using audio-visual media on increasing knowledge about preventing early marriage at SMPN 1 Sambeng. Methods: The research design used was a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 62 seventh-grade students selected through simple random sampling. This study was conducted on February 13, 2025, at SMPN 1 Sambeng. The intervention, in the form of an educational video about early marriage, was conducted once, followed by measuring the level of knowledge before and after the intervention using a questionnaire. Data analysis was conducted using the Wilcoxon test. Results: The research results showed an increase in the average knowledge of seventh-grade students about the prevention of early marriage, from a pretest score of 71.85 to a posttest score of 91.1. The study was conducted on seventh-grade students with a total of 41 male and 21 female participants. Conclusion: The results of the study showed a significant increase in the level of student knowledge after receiving health education through audio-visual media. It can be concluded that audio visual media is effective in increasing students' knowledge about early marriage. Keywords: Audiovisual, Early marriage, Health education,  Knowledge, Youth.